Perbedaan Kadar Trigliserida Menggunakan Alat Spektrofotometer Uv-Vis dengan Fotometer pada Mahasiswa Obesitas di Universitas ‘Aisyiyah Yogyakarta - Mar’atun Soalihah; Arifiani Agustin Amalia; Yuyun Nailufar; Mar'atunSoalihah (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Laboratory tests are used to help diagnose diseases. One of them is the examination of triglyceride levels which is generally performed on obese patients who have a history of cardiovascular disease, type 2 diabetes mellitus, and hypertension. The most commonly used equipment for examining triglycerides are uv-vis spectrophotometers and photometers. The difference between a UV-vis spectrophotometer and a photometer lies in the monochromator. The photometer does not have a monochromator, however the UV-vis spectrophotometer has a monochromator, that functions to eliminate unwanted wavelengths of light components that are not needed for the examination, making it more selective. This study aims to determine the differences in the results of triglyceride level examinations using a UV-vis spectrophotometer and a photometer. This study was a descriptive-analytical study with a cross-sectional approach. The results showed a sig value (2-tailed) of 0.112> 0.05, which means that there is no significant difference in the results of triglyceride examinations with a UV-vis spectrophotometer and a photometer in obese students at Universitas 'Aisyiyah Yogyakarta. Medical Laboratory Technologists are required to regularly and consistently conduct quality control in order to ensure the accuracy and reliability of test results.